Achieving low-temperature wafer level bonding with Cu-Sn-In ternary at 150 °C. (1st January 2023) - Golim, Obert; Vuorinen, Vesa; Ross, Glenn; Wernicke, Tobias; Pawlak, Marta; Tiwary, Nikhilendu; Paulasto-Kröckel, Mervi
Abstract: In this work, a low-temperature wafer-level bonding process at 150 °C was carried out on Si wafers containing 10 µm-sized microbumps based on the Cu-Sn-In ternary system. Thermodynamic study shows that addition of In enables low-melting temperature metals to reach liquid phase below In melting point (157 °C) and promotes rapid solidification of the intermetallic layer, which are beneficial for achieving low-temperature bonding. Microstructural observation shows high bonding quality with low amount of defect. SEM and TEM characterization concludes that a single-phase intermetallic formed in the bond and identified as Cu6 (Sn, In)5 with a hexagonal lattice. Mechanical tensile test indicates that the bond has a mechanical tensile strength of 30 MPa, which are adequate for 3D heterogeneous integration. Graphical abstract: Image, graphical abstract